A cross-sectional study of the prevalence, awareness, treatment and control of hypertension in Shenzhen, China. Issue 6 (15th June 2017) - Li, Haitao; Yan, Xinfeng; Deng, Xiaoting; Yang, Lizhen; Zhao, Shaojuan; Zou, Jianfeng; Luo, Yi; Cao, Sijing
Abstract : Objectives: An understanding of the awareness, treatment and control of hypertension is helpful to guide decision-making regarding interventions to reduce the risk for diseases with hypertension as a key risk factor. This study aimed to estimate the prevalence, awareness, treatment, and control of hypertension in Shenzhen, China. Methods: A cross-sectional study was conducted. We employed multistage cluster random sampling methods to select participants. A survey involving face-to-face interviews was conducted to collect the data. A total of 1676 participants finished the survey and formed the final analysis. Results: We found that the prevalence of hypertension was 17.6%. The rates of hypertension awareness, treatment and control were 48.8%, 51.4% and 43.2% respectively. Only 6.8% hypertensives were found to be managed by community health centres. Compared with the female participants, the males were found to have higher rates of prevalence (19.7% vs 15.7%; OR 1.47, 95% CI 1.10 to 1.97) and awareness (42.9% vs 38.1%; OR 2.35, 95% CI 1.28 to 4.33), but lower rates of medication treatments (20.5% vs 30.2%; OR 0.83, 95% CI 0.05 to 0.92) and control (12.8% vs 23.0%; OR 0.45, 95% CI 0.21 to 0.96). Migrants were more likely to be aware of hypertension (32.5% vs 44.3%; OR 0.57, 95% CI 0.30 to 0.90), reduce their salt intake (8.8% vs 18.1%; OR 0.40, 95% CI 0.15 to 0.94), and undertake regular monitoring of hypertension (1.3% vs 11.0%; OR 0.14, 95% CI 0.02 to 0.92) when compared with the locals. Conclusions: Our study finds that hypertension is an important public health burden in Shenzhen. It implies that strategies need to be developed to improve effective primary care management of hypertension. It also suggests a need to develop gender and household register tailored strategies for the prevention, detection, treatment and control of hypertension.